Teacher and Student Talk in Virtual Classroom Interaction in Linguistics Lectures - Sari, Nopita; Rido, Akhyar (Universitas Teknokrat Indonesia, 2024)
In classroom interaction, university teacher or lecturer is required to be a facilitator to lead discussion. The university teacher or lecturer must transfer knowledge and ensure that the learning process is active and the material being taught is well received. Students must also take a role in the interactions in the classroom which are intended to foster confidence and understanding in the learning process. The objective of this research is to find out what type of teacher talk and student talk that occurred during virtual linguistics lectures interaction. In this research, the researcher used Foreign Language Interaction (FLINT) as the conceptual framework. Meanwhile, this research was conducted qualitatively. Data were collected through video-recoding of two virtual linguistics lectures in a university in Indonesia. Data were analyzed using Miles and Huberman (1994) which included data reduction, data display and drawing conclusion. The findings revealed that teacher and student talk were found during the two lectures with teacher talk which was more dominant than student talk. Teacher talk consisted of some categories, including giving information, giving directions, praise and encouragement, asking question, correct without rejection, criticizes students’ behavior and uses the idea of the student. Meanwhile, student talk comprised student response initiate and student response specific. In conclusion, teacher dominates the interaction in virtual classroom and has an important role in leading the class and directing students to actively interact.